Chapter 9: Porphyrinoids for Photodynamic Therapy - Senge, Mathias (My University, 2021)
This chapter gives an overview of porphyrinoids for use in photodynamic therapy. It covers the characteristics, properties, and current treatments or porphyrin-based photosensitizers. The first section introduces the phototherapy and photodynamic therapy concepts and gives an overview of the principles of photophysical and photopharmacological aspects of potential photosensitizers. The subsequent section summarizes current treatments of clinically approved photosensitizers and those under development. A brief survey of the strategies for singlet oxygen generation enhancement and drug-delivery improvements is described in the last section.
Keywords: porphyrinoids; photosensitizers; phototherapy; porphyrinoids; photosensitizers; phototherapy